Sosialisasi Jejak Peradaban Nusantara: Eksplorasi Peninggalan Sejarah di Indonesia dalam Pembelajaran IPS Kelas V SD - Sari Mahwati Hasibuan; Saidah Oktariyati; M Muthma'innah; Syamsidah Lubis (SIGMA : Jurnal Sinergi Mengabdi, 2025)
This community service aims to socialize the traces of the Nusantara civilization, which can be optimized as a learning resource in social science education. Social science provides the intellectual foundation for evaluating historical artifacts. History at the elementary school level plays a crucial role in shaping students' national identity and patriotic values. The main focus of this research is on the utilization of historical relics such as temples, inscriptions, statues, and cultural artifacts scattered throughout various regions of Indonesia. In addition, it aims to make learning more contextual, meaningful, and interesting for students. The research method used is AssetBased Community Development, which is a community empowerment method that emphasizes the identification and utilization of existing resources and capabilities within the community. Meanwhile, the data collection techniques in this method consist of documentation such as lesson plans and textbooks. The research findings indicate that integrating historical artifacts into social studies curriculum not only enhances students' interest and motivation in learning but also strengthens their understanding of the development of Indonesian civilization over time. Furthermore, this approach fosters an appreciation for culture, tolerance, love for the homeland, and a sense of ownership toward the nation's ancestral heritage. These findings recommend the need for innovative, locally-based cultural learning approaches and teacher training in developing teaching strategies that connect historical content with the students' surrounding environment.